An assessment of the usability of Science and Technology Academic and Research-Based Openly-Operated Kiosk Station (STARBOOKS) based on user perception - Carretero, Sheila Marie O. (2012)
The existence of computers provided efficiency by allowing information to be accessible. To cope with modernization, libraries are adopting a new approach in providing its services, thus resulting to the emergence of digital library (DL).